Middle phalanx base fractures managed with Suzuki frame: a series of 23 patients - Bhat, Nawaz Ahmad; M., John; Lone, Zubair Ahmad; Bhat, Tanveer Ahmed; Ghani, Abdul; Butt, Mohammed Farooq; Gupta, Sanjeev (International Journal of Research in Orthopaedics, 2023)
Background: Intra-articular fractures of the base of middle phalanx are difficult to manage. With many known methods of treatment available, the authors present their experience of managing these injuries by Suzuki’s pin and rubber traction method. Methods: A prospective study of five years duration which included 23 patients. All the patients were managed with Suzuki’s pin and rubber traction system. The primary outcome variable was ROM at the PIP joint. The secondary outcome variable was the complication profile. Results: The mean ROM at the PIP joint at the final follow-up was 80±12.2 (range: 50-100) degrees. The mean flexion at PIP joint at the final follow-up was 82.72±10.5 degrees and the mean extension at PIP joint was -2.7±4.5 degrees. No case of non-union was observed in the present study. Pin tract infection occurred in 17.39% of cases and was the commonest complication observed. Two patients needed realignment of K-wires for pin displacement. One patient developed osteomyelitis of middle phalanx at three weeks and needed early removal of hardware. The same patient also developed complex regional pain syndrome (CRPS) at two months. One patient developed painful arthritis of PIP joint. Conclusions: Suzuki’s pin and rubber traction method is an effective modality of treatment for intra-articular fractures of the base of proximal phalanx of fingers of hand. Although, not free of complications the final results in most patients are good. However, the authors recommend large randomized control trials to be held for these injuries to compare carious modalities of treatment.